Sesame (Sesamum indicum) in the rice fallow environment - a critical appraisal: SESAME (SESAMUM INDICUM) IN THE RICE FALLOW ENVIRONMENT - A CRITICAL APPRAISAL - K RAMESH,; P RATNAKUMAR,; C HARISUDAN,; S BHASKAR,; A VISHNUVARDHAN REDDY, (Journal of Oilseeds Research, 2019)
Rice fallow sesame in the states of Tamil Nadu, Andhra Pradesh, Telangana, Odisha and to a limited extent in eastern Indian states, is an opportunity for horizontal expansion of sesame area and its production in the country. The productivity of sesame remains abysmally low as compared to the world average and research efforts needs to be focused to enhance the productivity of this crop which has a huge potential for export. Unlike rice fallow pulses cultivation, sesame cultivation needs concerted efforts to enhance its productivity in rice fallows. This review critically appraises the rice fallow environments in general, determinants of sesame production in this fragile environment and efforts needed for the successful area expansion of sesame crop in the country.